Adakah Perbedaan Gender Minat Mahasiswa Menjadi Wirausaha Dilihat Dari Efikasi Diri? (Studi Kasus Mahasiswa Fakultas Ekonomi Universitas Sangga Buana YPKP Bandung) - Bagus Efan Sanusi; Nenny Hendajany; Noviani Dewi (Jurnal Ekonomi Manajemen Perbankan, 2022)
This study aims to find out whether there are gender differences in students' interests seen from their self-efficacy. The first research problem is to find out whether there is an effect of self-efficacy on the interest in entrepreneurship, and secondly, is there a gender difference in the interest in entrepreneurship seen in self-efficacy. The case was taken at the Faculty of Economics, Sangga Buana University. Quantitative research methods are used to answer research problems by taking primary data. The amount of data collected was 93 respondents with a sampling approach using the Slovin formula, consisting of 39 men and 54 women. The data analysis technique used is descriptive associative. The gender variable is included in the model in the form of a dummy variable. The results of the study show that there is an effect of self-efficacy on student interest, but there is insufficient evidence of gender differences in this regard. The implication of this research is the need to increase self-efficacy in students in every lesson so that there is more interest in entrepreneurship.